The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pharmaceutics12080706
|View full text |Cite
|
Sign up to set email alerts
|

Fasudil Loaded PLGA Microspheres as Potential Intravitreal Depot Formulation for Glaucoma Therapy

Abstract: Rho-associated protein kinase (ROCK) inhibitors allow for causative glaucoma therapy. Unfortunately, topically applied ROCK inhibitors suffer from high incidence of hyperemia and low intraocular bioavailability. Therefore, we propose the use of poly (lactide-co-glycolide) (PLGA) microspheres as a depot formulation for intravitreal injection to supply outflow tissues with the ROCK inhibitor fasudil over a prolonged time. Fasudil-loaded microspheres were prepared by double emulsion solvent evaporation technique.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…According to the literature, depurination is pH-dependent; the more acidic, the more depurination [ 73 ]. In addition, high temperature (37 °C) favors PLGA degradation into lactic and co-glycolic acids, which progressively acidify the medium [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, depurination is pH-dependent; the more acidic, the more depurination [ 73 ]. In addition, high temperature (37 °C) favors PLGA degradation into lactic and co-glycolic acids, which progressively acidify the medium [ 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…To cope with this shortcoming, a depot formulation containing the NPs would be ideal in the long run. Such a depot would be applied intraocularly, for example, into the vitreous body [ 52 ]. After release from the depot, the NPs would reach the anterior chamber and be distributed to the trabecular meshwork.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to take into consideration the mode of administration as most of the glaucoma preclinical and clinical studies are based on topical applied ophthalmic solutions, having been demonstrated their safety profile and hypotensive properties but with a high incidence of conjunctival hyperaemia and with limited intraocular bioavailability due to the short corneal residence time and their characteristic hydrophilic properties [ 137 , 139 , 140 , 141 , 142 ]. This is one reason under the high rate of studies based on intravitreal injections for pathologies involving the posterior segment of the eye, trying to increase the intraocular active-drug concentration [ 143 , 144 ].…”
Section: From the Bench To The Bedsidementioning
confidence: 99%